A polycarbonate modified material for 3D printing with low printing temperature, a preparation method thereof, and a printing filament

By adding aliphatic aromatic copolyester and vinyl acetate copolymer to the polycarbonate, the problem of high temperature in 3D printing is solved, low-temperature printing is achieved, and energy consumption is reduced.

CN114507431BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011158032.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-26
Publication Date
2025-03-04
Estimated Expiration
2040-10-26

AI Technical Summary

Technical Problem

Existing polycarbonates require higher print nozzle temperature and base plate temperature during 3D printing, resulting in harsh printing conditions and waste of energy.

Method used

The material is modified to reduce the processing temperature of 3D printing by adding aliphatic aromatic copolyester and vinyl acetate copolymer to the polycarbonate.

Benefits of technology

3D printing is achieved at lower nozzle temperatures (220℃) and base plate temperatures (80℃), and the printing effect is not affected, reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114507431B_ABST
    Figure CN114507431B_ABST
Patent Text Reader

Abstract

The present invention relates to a polycarbonate modified material for 3D printing with low printing temperature, a preparation method thereof and a printing filament. The polycarbonate modified material comprises 65 to 80 parts of polycarbonate, 20 to 35 parts of aliphatic aromatic copolyester and 1 to 5 parts of vinyl acetate copolymer, and a polycarbonate blended modified material is obtained by twin-screw melt extrusion, and then a filament that can be used for 3D printing is prepared by a single-screw extrusion wire drawing device. The print head temperature of the polycarbonate modified material can be reduced to 220°C, the base plate temperature can be reduced to 80°C, and the warping curvature can be controlled within 1.0m ‑1 Below, normal printing is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials, and in particular to a polycarbonate modified material for 3D printing with low printing temperature (nozzle temperature, base plate temperature), a preparation method thereof, and a printing filament. Background Art

[0002] 3D printing is an emerging rapid prototyping technology, known as "manufacturing technology with industrial revolution significance". It can meet the ever-increasing personalized needs, achieve a breakthrough in traditional manufacturing technology, and is also considered to be the technical representative of the "third industrial revolution". It is widely used in industrial production, civil, aerospace, military, medical and other fields. It is a technology based on digital model files, which finally obtains the required objects by printing layer by layer. Up to now, there are five main process technologies that are the most mature and widely used, including stereolithography (SLA), laminated object manufacturing (LOM), fused deposition modeling (FDM), selective laser sintering (SLS), and selective laser melting (SLM). Among the five technologies, fused deposition modeling technology is a technology with the most widely used materials and the longest development time. It is also a technology that can be miniaturized and used in daily life.

[0003] At present, the thermoplastic printing plastics commonly used in FDM technology include acrylonitrile-butadiene-styrene copolymer (ABS), polylactic acid (PLA), nylon (PA), high-impact polystyrene (HIPS), polycarbonate (PC), etc. Compared with other printing materials, PC has good transparency, insulation, excellent mechanical properties and thermal stability, and is an engineering material with excellent comprehensive performance. However, in 3D printing, due to the printer principle of FDM itself and the high processing temperature of PC, higher print head temperature and base plate temperature are required to achieve printing, the printing conditions are relatively harsh, and energy is wasted.

[0004] In the present invention, by adding aliphatic aromatic copolyesters and vinyl acetate copolymers to modify PC materials, the processing temperature (nozzle temperature and base plate temperature) of the obtained PC modified material for 3D printing is reduced to a certain extent without affecting normal printing. Summary of the invention

[0005] In order to solve the problems of excessively high temperature of polycarbonate printing nozzles and excessively high temperature of base plates in the above prior art, the present invention provides a polycarbonate modified material and printing filament for 3D printing, which improves the problem of excessively high processing temperature of polycarbonate 3D printing by adding aliphatic aromatic copolyesters and vinyl acetate copolymers to PC raw materials.

[0006] One of the purposes of the present invention is to provide a polycarbonate modified material for 3D printing with a low printing temperature, wherein the material comprises the following components in parts by weight:

[0007] (1) 65 to 80 parts of polycarbonate, preferably 70 to 80 parts of polycarbonate;

[0008] (2) 20 to 35 parts of aliphatic aromatic copolyesters, preferably 20 to 30 parts of aliphatic aromatic copolyesters;

[0009] (3) 1 to 5 parts of vinyl acetate copolymer, preferably 1 to 4 parts of vinyl acetate copolymer.

[0010] The temperature of the 3D printing nozzle of the polycarbonate modified material of the present invention is reduced to 220° C., the temperature of the base plate is reduced to 80° C., and the printing effect is not affected.

[0011] In the above technical solution, the polycarbonate is a high molecular polymer containing carbonate groups in the molecular chain, and is at least one of aliphatic polycarbonate, alicyclic polycarbonate and aromatic polycarbonate, and bisphenol A polycarbonate is more preferred.

[0012] In the above technical solution, the molecular chain segment of the aliphatic aromatic copolyester contains one or more aliphatic diol units, at least one of aliphatic diacid or aliphatic diacid anhydride, aliphatic diacyl halide, and aliphatic diacyl ester units, and at least one of aromatic diacid or aromatic diacid anhydride, aromatic diacyl halide, and aromatic diacyl ester units.

[0013] The aliphatic aromatic copolyesters in the present invention include linear and branched copolyesters. One or more branching agents are added during the synthesis of the branched copolyesters. The branching agent is generally a polyacid with two or more carboxyl groups, a polyol or polyhydroxy acid with two or more hydroxyl groups, etc. Applicable branching agents include glycerol, trimethylolethane, trimethylolpropane, 1,2,4-butanetriol, pentaerythritol, 1,2,6-hexanetriol, sorbitol, 1,2,3-benzenetricarboxylic acid (hemimellitic acid), 1,2,4-benzenetricarboxylic acid (triimellitic acid), 1,3,5-benzenetricarboxylic acid (trimesic acid) and acid anhydrides, etc.

[0014] The aliphatic aromatic copolyester is preferably polyethylene terephthalate-co-oxalate, polyethylene terephthalate-co-malonate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-suberate, poly(propylene terephthalate)-co-oxal ...succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-suberate, polyethylene terephthalate-co-oxalate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-succinate propylene glycol formate-co-malonate, polypropylene glycol terephthalate-co-succinate, polypropylene glycol terephthalate-co-glutarate, polypropylene terephthalate-co-adipate, polypropylene terephthalate-co-suberate, polypropylene terephthalate-co-sebacate, polybutylene terephthalate-co-oxalate, polybutylene terephthalate-co-malonate, polybutylene terephthalate Polybutylene terephthalate-co-succinate, polybutylene terephthalate-co-glutarate, polybutylene terephthalate-co-adipate, polybutylene terephthalate-co-suberate, polyhexylene terephthalate-co-oxalate, polyhexylene terephthalate-co-malonate, polyhexylene terephthalate-co-succinate, polyhexylene terephthalate-co-glutarate, poly At least one of poly(hexylene terephthalate-co-adipate), poly(hexylene terephthalate-co-suberate), etc., preferably at least one of poly(butylene terephthalate-co-adipate), poly(ethylene terephthalate-co-adipate), poly(ethylene terephthalate-co-succinate), poly(butylene terephthalate-co-succinate), more preferably poly(butylene terephthalate-co-adipate).

[0015] In the above technical solution, the vinyl acetate copolymer contains different contents of polyvinyl acetate segments and has a copolymer with a lower processing temperature (150°C), preferably an ethylene-vinyl acetate copolymer with a VA content of 10 to 28%, and further preferably an ethylene-vinyl acetate copolymer with a VA content of 15 to 25%.

[0016] The vinyl acetate copolymer can be, for example, V4110D, V3110F, V5110F, V4610H, V3510K, V3610F, V4110F, V2510J, V3610J, V4110J, V5110J, V5110K, V5110H, V6110M, V6110MC, etc. produced by BASF.

[0017] In the above technical solution, the polycarbonate modified material has a warping curvature of less than 1.0 mm when the 3D printing nozzle temperature is 220°C and the base plate temperature is 80°C. -1 .

[0018] The second object of the present invention is to provide a method for preparing the polycarbonate modified material, comprising blending and extruding components including the polycarbonate, aliphatic aromatic copolyester, and vinyl acetate copolymer to obtain the polycarbonate modified material.

[0019] Among the above technical solutions, the twin-screw extrusion method is preferred.

[0020] In the above technical solution, preferably, the required amounts of polycarbonate, aliphatic aromatic copolyester, and vinyl acetate copolymer are fully mixed in a mixing device, then blended and extruded in a twin-screw extruder, granulated and dried; to obtain the polycarbonate modified material for 3D printing.

[0021] In the above technical solution, further, the rotation speed of the twin-screw extruder is 50-150 rpm; and the extrusion temperature is 200-250°C.

[0022] The third object of the present invention is to provide a 3D printing filament for FDM, which is prepared from the polycarbonate modified material.

[0023] The temperature of the print head of the FDM 3D printing filament can be reduced to 220°C, the temperature of the base plate can be reduced to 80°C, and the warping curvature can be controlled within 1.0m. -1 Below, normal printing is not affected.

[0024] A fourth object of the present invention is to provide a method for preparing the 3D printing filament for FDM, comprising continuously melt-extruding the polycarbonate modified material and obtaining the 3D printing filament by oriented drawing.

[0025] In the above technical solution, continuous melt extrusion is adopted to melt and extrude the polycarbonate modified material for 3D printing in a screw extruder, cool it, and then orient and stretch it to obtain the polycarbonate 3D printing wire.

[0026] In the above technical solution, the single-screw extrusion method is preferred, in which the material is melt-extruded by a single-screw extruder, cooled in two water baths at different temperatures, and simultaneously stretched and wound to form a 3D printing line.

[0027] In the above technical solution, further, the single-screw continuous extrusion temperature is preferably 210-225° C.; the rotation speed is preferably 12.0-14.0 rpm.

[0028] In the above technical solution, further, the traction frequency of the drafting device is preferably 2.5 to 3.5.

[0029] The present invention adopts vinyl acetate copolymer to improve the low-temperature printing performance of PC / copolyester, which can effectively reduce the printing processing temperature of PC 3D printing materials, is conducive to the release of internal stress of the material, reduces the molding difficulty of 3D printing, and improves the warping and hue of the printed spline. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The DSC data of each PC modified material and raw material in the embodiments and comparative examples are the temperature rise curves.

[0031] Figure 2 The warping curvature data of each PC modified material in the examples and comparative examples at different print head temperatures (A) and base plate temperatures (B).

[0032] Figure 3 The warping curvature data of each PC modified material in the examples and comparative examples at different print head temperatures (A) and base plate temperatures (B).

[0033] Figure 4 The following are photos of 3D printed specimens of PC modified materials of the embodiments and comparative examples. DETAILED DESCRIPTION

[0034] The present invention is specifically described by the following examples. It is necessary to point out that the following examples are only for further explanation of the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above invention.

[0035] The present invention performs performance measurement according to the following method:

[0036] Melt flow index (MFR) measurement method: According to ISO 1133 standard, Instron CEAST MF20 melt index meter is used for measurement, barrel temperature is 250°C, weight load is 5kg, die diameter is 2.095mm, length is 8mm, preheating time is 4min, automatic sample cutting is performed at set time intervals, and the average value is calculated for 5 times. The measurement result is expressed in grams per 10 minutes (g / 10min).

[0037] Thermal performance analysis (DSC): The test was carried out on a Discovery series differential scanning calorimeter (DSC) produced by TA Instruments. The processing software was TA Instruments Trios version 3.1.5. The DSC instrument was equipped with a TA Refrigerated Cooling System 90 mechanical refrigeration accessory. The test atmosphere was 50 mL / min of nitrogen, and the sample amount required for the test was 5 to 10 mg. The test procedure is as follows: first stabilize the temperature at 40°C, then increase the temperature to 250°C at 10°C / min and keep the temperature constant for 1 minute to remove the thermal history, then cool down to -50°C at 10°C / min, and then increase the temperature to 250°C at 10°C. Record the cooling process and the second heating process to study the thermal properties of the sample. Through the DSC test, the software can directly derive the glass transition ("T g ”), melting temperature (“T m ”) and other information.

[0038] [Examples 1-3]

[0039] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Dry in a vacuum oven at 120℃ for 5h to remove moisture. Polybutylene adipate terephthalate (PBAT) is produced by BASF, Germany, with the brand name C1200. Vinyl acetate copolymer (EVA) is produced by BASF of Germany, with the brand name EVA-V5110J, and its VA content is 18.5%, melting point is 84.8℃, and melt index is 2.7g / 10min (2.16kg / 190℃). The two particles are dried in a vacuum oven at 60℃ for 5h to remove moisture. Then they are mixed in a mixer according to the specific ratio of PC / PBAT of 80 / 20 by mass, and the mixing time is 20min; then 1 part, 2 parts, and 4 parts of EVA copolymer are added to the PC blend respectively, and mixed in the mixer, and the mixing time is 10min. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States is used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are: 210°C, 220°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, 230°C, and 230°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC / PBAT-1%EVA, PC / PBAT-2%EVA, PC / PBAT-4%EVA, respectively, and then pumped in a vacuum drying oven at 60°C for 4 hours and packaged for use.

[0040] [Example 4]

[0041] All three particles, as well as raw materials PC, PBAT, and EVA, were subjected to differential scanning calorimetry (DSC) tests according to the steps described above. The second heating curve ( Figure 1 The crystallization temperature (“T c ”), melting temperature (“T m ”), glass transition (“T g ”), and other information, the values ​​are listed in Table 1.

[0042] Table 1 Thermal performance parameters of each particle obtained from DSC results.

[0043]

[0044] Polycarbonate modified material presents uniform milky white color. Figure 1From Table 1, we can see that only one glass transition temperature appears after blending and it is between the glass transition temperatures of PC and PBAT, which proves that the three components PC, PBAT and EVA have good compatibility, and within the prepared content range, as the EVA content increases, the glass transition temperature gradually decreases. For example, after adding 2% EVA to PC / PBAT, the glass transition temperature of the material decreases from 144.4℃ to 87.8℃.

[0045] [Example 5]

[0046] The three kinds of particles obtained in Examples 1-3 and PC raw materials were subjected to melt index measurement in an Instron CEAST MF20 melt index meter. The results are shown in Table 2.

[0047] Table 2 Melt index of various materials at 250℃ and 5kg

[0048]

[0049] From Table 2, we can see that at 250°C and 5kg, with the addition of EVA, the fluidity of the blend decreases slightly within the addition range of 1% to 4%, but the change is small.

[0050] [Example 6]

[0051] The 3D printing wire was prepared by a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. It consists of a single screw extruder, two water bath cooling structures of hot water bath and cold water bath, and winding parts. A die with a diameter of about 2 mm is configured. The particles prepared in Example 1 are added to the feeder in batches, with about 1.5 kg of sample for each component. The feeder maintains a temperature of 80°C and blast drying. The single screw speed and roller speed are adjusted, and the diameter of the wire is controlled by adjusting the traction speed. The specific parameters are shown in Table 3.

[0052] Table 3 Processing conditions of 3D printing filaments

[0053]

[0054] As shown in Table 3, although the glass transition temperature and fluidity of samples with different composition contents are different, it is necessary to adjust the processing temperature, screw speed, roller speed, etc. to control the filament to about 1.73 mm, so that it can be applied to FDM 3D printing. The composition containing EVA can be extruded at a lower temperature, saving energy.

[0055] [Example 7]

[0056] The 3D printing filament prepared in Example 6 was 3D printed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a cuboid of 150.0mm×15.0mm×4.0mm, the printing parameters are standard resolution, the nozzle extrusion speed is 90mm / s, the moving speed is 90mm / s, the spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the bottom plate temperature is 100℃; at the same time, the nozzle temperature is controlled to 250℃, and the bottom plate temperature is set to 70℃, 80℃, 90℃, and 100℃. Under the above conditions, pure PC printing filaments cannot be printed normally, and the spline warping is very obvious. Under the same conditions, when the print head temperature is above 220℃ and the base plate temperature is above 80℃, the warping of PC / PBAT-1%EVA, PC / PBAT-2%EVA, and PC / PBAT-4%EVA is not obvious, and they can all print normally, indicating that adding EVA can effectively reduce the temperature of the nozzle and base plate. Considering the spline as a part of the arc, and calculating the warping according to the curvature calculation method, the line graph of the spline curvature is shown in Figure 2 . The intuitive comparison of the samples under the printing conditions of 230℃ / 100℃ is shown in Figure 3 .from Figure 3 It can be seen that by placing the spline on a flat table and comparing it, it can be found that as the EVA content increases, the flatness of the spline becomes better.

[0057] As the EVA content increases, the printing performance of the blend is further improved. When the content reaches 4 parts, PC / PBAT-4% EVA shows excellent printing performance, and the curvature of the spline at 220℃ / 100℃ is only 0.42m -1 ; The curvature of the spline at 250℃ / 80℃ is 0.43m -1 .

[0058] [Example 8]

[0059] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111 was dried in a vacuum oven at 120°C for 5 hours to remove moisture. Polybutylene adipate terephthalate (PBAT) was produced by BASF, Germany, with the brand name C1200. Ethylene acetate copolymer (EVA) is produced by BASF, Germany, with the brand name EVA-V5110J. The two particles were dried in a vacuum oven at 60°C for 4 hours to remove moisture. Then, they were mixed in a mixer according to the matrix resin mass ratio of PC / PBAT 70 / 30, and the mixing time was 20 minutes; then, 2 parts of EVA copolymer were added to the PC blend, and mixed in the mixer for 10 minutes. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 200°C, 200°C, 220°C, 220°C, 220°C, 230°C, 230°C, 230°C and 230°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the spline is extruded from the die and air-cooled, it is cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC-30%PBAT-2%EVA, and then they are pumped in a vacuum drying oven at 60°C for 4 hours and then packaged for use.

[0060] The above sample PC-30% PBAT was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the traction speed. The final wire diameter was 1.66-1.73 mm.

[0061] Spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a rectangular parallelepiped of 150.0.mm×15.0mm×4.0mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, movement speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the base plate temperature is 100℃; at the same time, the nozzle temperature is controlled to 250℃, and the base plate temperature is set to 80℃, 90℃, and 100℃. Under this condition, when the PC-30%PBAT-2%EVA print head temperature is above 220℃ and the base plate temperature is above 80℃, the warping is not obvious and can be printed normally. The line graph of the calculated spline curvature is shown in Figure 3 .

[0062] [Example 9]

[0063] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111, dried in a vacuum oven at 120℃ for 5h to remove moisture. Polybutylene succinate terephthalate (PBST) is produced by Sinopec Yizheng Chemical Fiber Co., Ltd., with the brand name TS159. Vinyl acetate copolymer (EVA) is produced by BASF of Germany, with the brand name EVA-V5110J. The two particles were dried in a vacuum oven at 60℃ for 4 hours to remove moisture. Then, they were mixed in a mixer according to the matrix resin mass ratio of PC / PBST 80 / 20, and the mixing time was 20min; then, 4 parts of EVA copolymer were added to the PC blend, and mixed in the mixer, and the mixing time was 10min. Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 220°C, 220°C, 240°C, 240°C, 240°C, 240°C, 250°C, 250°C, 250°C and 250°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC-20% PBST-2% EVA, and then they are packaged for use after being pumped in a vacuum drying oven at 60°C for 4 hours.

[0064] The above sample PC-20% PBST-2% EVA was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the pulling speed. The final wire diameter was 1.68-1.76 mm.

[0065] Spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a rectangular parallelepiped of 150.0.mm×15.0mm×4.0mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, movement speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the base plate temperature is 100℃; at the same time, the nozzle temperature is controlled to 250℃, and the base plate temperature is set to 80℃, 90℃, and 100℃. Under this condition, when the PC-20%PBST-2%EVA print head temperature is above 220℃ and the base plate temperature is above 80℃, the warpage is controlled below 1.0, meeting normal printing conditions. The line graph of the calculated spline curvature is shown in Figure 3 .

[0066] [Comparative Example 1]

[0067] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Polybutylene adipate terephthalate (PBAT) is produced by BASF of Germany with the brand name C1200. The two particles were dried in a vacuum oven at 120°C for 4 hours to remove moisture. Then they were mixed in a mixer according to the matrix resin mass ratio of PC / PBAT 80 / 20, and the mixing time was 20 minutes. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are: 210°C, 220°C, 230°C, 230°C, 230°C, 240°C, 240°C, 240°C, 240°C and 240°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3 mm. After the sample strip is extruded from the die and air-cooled, it is cut into cylindrical particles with a set diameter of about 3 mm by a pelletizer. The above particles are named PC-20% PBAT, and then they are dried in a vacuum oven at 60°C for 4 hours and packaged for use.

[0068] The above sample PC-20% PBAT was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the traction speed. The final wire diameter was 1.68-1.76 mm.

[0069] The spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a 150.0mm×15.0mm×4.0mm cuboid, the printing parameters are the resolution (resolution) as standard, the nozzle extrusion speed is 90mm / s, the moving speed is 90mm / s, the spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the bottom plate temperature is 100℃; at the same time, the nozzle temperature is controlled to 250℃, and the bottom plate temperature is set to 80℃, 90℃, and 100℃. Under this condition, PC-20% PBAT can control the curvature below 1 when the print head temperature is 240-250°C. When the print head temperature drops to 220-230°C, the curvature increases significantly, which is about one to two times higher than the formulation of the present invention, and normal printing cannot be achieved; when the base plate temperature drops to 90°C, normal printing cannot be achieved ( Figure 2 ).

[0070] [Comparative Example 2]

[0071] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and has a brand name of LEXANTM Resin HF1130-111. It is dried in a vacuum oven at 120°C for 5 hours to remove moisture. Polybutylene adipate terephthalate (PBAT) is produced by BASF of Germany and has a brand name of C1200. Ethylene acetate copolymer (EVA) is produced by BASF, Germany, with the brand name EVA-V5110J. The two particles were dried in a vacuum oven at 60°C for 4 hours to remove moisture. Then, they were mixed in a mixer according to the matrix resin mass ratio of PC / PBAT 85 / 15, and the mixing time was 20 minutes; then, 2 parts of EVA copolymer were added to the PC blend, and mixed in the mixer for 10 minutes. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 220°C, 220°C, 240°C, 240°C, 240°C, 240°C, 250°C, 250°C, 250°C and 250°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC-15% PBAT, and then they are packaged for use after being pumped in a vacuum drying oven at 60°C for 4 hours.

[0072] The above sample PC-15% PBAT was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the traction speed. The final wire diameter was 1.68-1.76 mm.

[0073] Spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a rectangular parallelepiped of 150.0.mm×15.0mm×4.0mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, moving speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the base plate temperature is 100℃; at the same time, the nozzle temperature is controlled to 250℃, and the base plate temperature is set to 80℃, 90℃, and 100℃. Under these conditions, the curvature of PC-15% PBAT is as high as 1.11 ( Figure 2 ), when the print head temperature drops to 230℃ and the base plate temperature drops to 80℃, normal printing cannot be achieved.

[0074] [Comparative Example 3]

[0075] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111. Vinyl acetate copolymer (EVA) is produced by BASF of Germany, with the brand name EVA-V5110J. The two particles were dried in a vacuum oven at 120℃ / 60℃ for 5h to remove moisture. Then they were mixed in a mixer according to the matrix resin mass ratio of PC / EVA95 / 5, and the mixing time was 20min. The Eurolab 16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States was used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 230°C, 240°C, 240°C, 250°C, 250°C, 250°C, 260°C, 260°C and 260°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 60% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC-NPBAT, and then they are packaged for use after being pumped in a vacuum drying oven at 60°C for 4 hours.

[0076] The above sample PC-NPBAT was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the pulling speed. The final wire diameter was 1.68-1.76 mm.

[0077] The spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a cuboid of 150.0mm×15.0mm×4.0mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, moving speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, 240℃, 230℃, 220℃, and the base plate temperature is 100℃. Under these conditions, PC-NPBAT warped severely and a complete spline could not be obtained.

[0078] [Comparative Example 4]

[0079] The polycarbonate (PC) used in the present invention is produced by Saudi Basic Industries Corporation and its brand is LEXAN TM ResinHF1130-111; polyethylene terephthalate (PET) is produced by DuPont, USA, with the brand name RE19051. The particles of both are dried in a vacuum oven at 120℃ for 5 hours to remove moisture. Vinyl acetate copolymer (EVA) is produced by BASF, Germany, with the brand name EVA-V5110J. The particles are dried in a vacuum oven at 60℃ for 4 hours to remove moisture. Then, the matrix resin is mixed in a mixer according to the mass ratio of PC / PET 80 / 20, and the mixing time is 20 minutes; then 4 parts of EVA copolymer are added to the PC blend, and mixed in the mixer for 10 minutes. Eurolab16 co-rotating twin-screw extruder (screw diameter 16mm, aspect ratio L / D=40) produced by Thermo Fisher Technology Company of the United States is used for extrusion granulation. The extruder has 11 sections from the feed port to the die, numbered 1-11, of which the first section only serves to add materials and cannot be heated. The temperatures of sections 2-11 of the extruder are 230°C, 230°C, 250°C, 250°C, 250°C, 250°C, 260°C, 260°C, 260°C and 260°C, respectively, and the screw speed is set at 100rpm. During stable operation, the torque is 55% of the maximum value. The extruder is equipped with a circular die with a diameter of 3mm. After the strips are extruded from the die and air-cooled, they are cut into cylindrical particles with a set diameter of about 3mm by a pelletizer. The above particles are named PC-20% PET, and then they are packaged for use after being pumped in a vacuum drying oven at 80°C for 4 hours.

[0080] The above sample PC-20% PET was prepared using a 3D printing wire forming extrusion line (model SHG) manufactured by Songhu Machinery Manufacturing Plant in Dongguan, China. About 1.5 kg of sample was added, and the feeder was kept at 80°C and air-dried. The single screw speed and roller speed were adjusted, and the diameter of the wire was controlled by adjusting the pulling speed. The final wire diameter was 1.69-1.73 mm.

[0081] The spline 3D printing was performed on a MakerBot Replicator 2X 3D printer. The spline parameters and printing parameters are as follows: the spline size is a rectangular parallelepiped of 150.0.mm×15.0mm×4.0mm, the printing parameters are standard resolution, nozzle extrusion speed is 90mm / s, moving speed is 90mm / s, spline filling rate is 100%, the height of each layer is 200μm, the nozzle temperature is set to 250℃, and the base plate temperature is 100℃. Under these conditions, the curvature of PC-20% PET is as high as 1.51. When the print head temperature and base plate temperature continue to decrease, normal printing can basically be achieved.

Claims

1. A polycarbonate modified material for 3D printing with low printing temperature, comprising the following components by weight: (1) 65 to 80 parts of polycarbonate; (2) 20 to 35 parts of aliphatic aromatic copolyester; (3) 1 to 5 parts of vinyl acetate copolymer; The aliphatic aromatic copolyester is polyethylene terephthalate-co-oxalate, polyethylene terephthalate-co-malonate, polyethylene terephthalate-co-succinate, polyethylene terephthalate-co-glutarate, polyethylene terephthalate-co-adipate, polyethylene terephthalate-co-suberate, poly(propylene terephthalate-co-oxalate), poly(propylene terephthalate-co-malonate), poly(propylene terephthalate-co-succinate), poly(propylene terephthalate-co-glutarate), poly(propylene terephthalate-co-adipate), poly(propylene terephthalate-co-suberate), poly(propylene terephthalate-co-oxalate). -co-propylene sebacate, polybutylene terephthalate-co-oxalate, polybutylene terephthalate-co-malonate, polybutylene terephthalate-co-succinate, polybutylene terephthalate-co-glutarate, polybutylene terephthalate-co-adipate, polybutylene terephthalate-co-suberate, polyhexylene terephthalate-co-oxalate, polyhexylene terephthalate-co-malonate, polyhexylene terephthalate-co-succinate, polyhexylene terephthalate-co-glutarate, polyhexylene terephthalate-co-adipate, and polyhexylene terephthalate-co-suberate.

2. The polycarbonate modified material according to claim 1, characterized in that By weight, it includes the following components: (1) 70 to 80 parts of polycarbonate; (2) 20 to 30 parts of aliphatic aromatic copolyester; (3) 1 to 4 parts of vinyl acetate copolymer.

3. The polycarbonate modified material according to claim 1, characterized in that: The polycarbonate is at least one of aliphatic polycarbonate, alicyclic polycarbonate and aromatic polycarbonate.

4. The polycarbonate modified material according to claim 3, characterized in that: The polycarbonate is an aromatic polycarbonate.

5. The polycarbonate modified material according to claim 4, characterized in that: The polycarbonate is bisphenol A type polycarbonate.

6. The polycarbonate modified material according to claim 1, characterized in that: The vinyl acetate copolymer is an ethylene-vinyl acetate copolymer with a VA content of 10 to 28%.

7. The polycarbonate modified material according to claim 6, characterized in that: The vinyl acetate copolymer is an ethylene-vinyl acetate copolymer with a VA content of 15-25%.

8. The polycarbonate modified material according to any one of claims 1 to 7, characterized in that: The polycarbonate modified material has a warping curvature of less than 1.0 mm when the 3D printing nozzle temperature is 220°C and the base plate temperature is 80°C. -1 .

9. A method for preparing a polycarbonate modified material according to any one of claims 1 to 8, comprising the following steps: The components including the polycarbonate, aliphatic aromatic copolyester and vinyl acetate copolymer are blended and extruded to obtain the polycarbonate modified material.

10. The method for preparing a polycarbonate modified material according to claim 9, characterized in that: The extrusion temperature is 200-250°C and the rotation speed is 50-150rpm.

11. A 3D printing filament for FDM, prepared from the polycarbonate modified material according to any one of claims 1 to 8.

12. A method for preparing a 3D printing filament for FDM according to claim 11, comprising continuously melt-extruding the polycarbonate modified material and obtaining the 3D printing filament by oriented drawing.

13. The method for preparing 3D printing filament according to claim 12, characterized in that: The extrusion temperature is 210-225°C and the rotation speed is 12.0-14.0 rpm; and / or, The traction frequency is 2.5~3.5.

Citation Information

Patent Citations

  • 3D printing aromatic polyester material and preparation method thereof

    CN103980672A

  • 3D-printing PC / PETG special material and preparation method thereof

    CN107383830A